COLL 41-studies in biosurfactants: sophorolipids - Momin, Shamim A.; Prabhune, Asmita; Sonchal, Bhushan P.; Shah, Sachin; Kothekar, Shrinivas C. (235th American-Chemical-Society National Meeting, 2008)
235th American-Chemical-Society National Meeting, New Orleans, LA, APR 06-10, 2008
Keywords: Biosurfactants; Candida bombicola ATCC 22214; Fermentation Process; sophorolipids

Microbial oxidation of medium chain fatty alcohol in the synthesis of sophorolipids by candida bombicola and its physicochemical characterization - Pulate, Vrushali Dengle; Bhagwat, Sunil S.; Prabhune, Asmita Ashutosh (Journal of Surfactants and Detergents, 2013)
Sophorolipids (SL) are glycolipid biosurfactants abundantly produced from different feedstocks by yeasts and have been widely developed for various applications. The amphipathic structures of sophorolipids imparts to them surfactant type properties. These biosurfactants are readily isolated in high yield and are nontoxic and biodegradable, which make them industrially interesting as surfactants or emulsifiers. Sophorolipid production was carried out using glucose as a hydrophilic source and lauryl alcohol C12-14, as a hydrophobic source by Candida bombicola (ATCC 22214). Process economics and environmental attractiveness was increased by using a low cost substrate. Optimization studies were carried out where the effect of glucose concentration, pH, temperature and metal ions on sophorolipid production was studied. Optimum production of sophorolipid obtained using lauryl alcohol (SLLA) was achieved after 96 h, the initial pH of the medium was 6.0 with 10 % glucose at 30 A degrees C. Primary characterization of SLLA was done by FTIR. The SLLA showed high physicochemical properties in terms of the surface activities when compared with synthetic surfactants including dodecyl tetraethylene glycol ether and sodium lauryl sulfate. The surface tension of SLLA thus obtained was found to be 24 mN/m with a critical micellar concentration (CMC) value of 0.68 mg/L. Antimicrobial testing showed that SLLA have potent antimicrobial activity against both gram negative bacteria, Escherichia coli (ATCC 8739) and gram positive cocci, Staphylococcus aureuss (ATCC 2079).
Keywords: Biosurfactants; Candida bombicola; CMC; Lauryl alcohol C12-14; sophorolipids; Surface tension

Antimicrobial and SEM studies of sophorolipids synthesized using lauryl alcohol - Dengle-Pulate, Vrushali; Chandorkar, Parul; Bhagwat, Sunil S.; Prabhune, Asmita Ashutosh (Journal of Surfactants and Detergents, 2014)
In recent years, researchers have developed biosurfactants for industrial, pharmaceutical and medical applications revealing the promising biological activities of these biomolecules. One of the best studied microbial surfactants are glycolipids, especially sophorolipids (SLs) produced by selected non-pathogenic yeast species of Candida. They are biodegradable, non-toxic and are environmentally friendly. Sophorolipid production was carried out using glucose as the hydrophilic source and lauryl alcohol C12-14, as the hydrophobic source using Candida bombicola ATCC 22214. Primary characterization of the SL obtained using lauryl alcohol (SLLA) was done by FTIR which depicted the presence of alkyl sophorosides/SLs. Antimicrobial activity testing revealed that SLLA showed complete inhibition against gram negative bacteria, Escherichia coli (ATCC 8739) Pseudomonas aeruginosa (ATCC 9027) at 30 and 1 mu g/ml at a contact time of 2 and 4 h respectively. Whereas for gram positive bacteria Staphylococcus aureus (ATCC 6358), Bacillus subtilis (ATCC 6633), complete inhibition was observed at 6 and 1 mu g/ml respectively at a contact time of 4 h. The formed SLLA showed noteworthy inhibition against the pathogenic yeast Candida albicans (ATCC 2091) at 50 mu g/ml with a contact time of 4 h. These values are remarkably low compared to reported values of oleic acid SLs and linolenic acid SLs which were studied for antimicrobial properties. Scanning electron microscopy analysis of the treated cells revealed the changes in morphology and topography of the microorganisms.
Keywords: Antimicrobial property; Biosurfactants; Candida bombicola; Lauryl alcohol; sophorolipids

Biodegradation of mixed polycyclic aromatic hydrocarbons by pure and mixed cultures of biosurfactant producing thermophilic and thermo-tolerant bacteria - Mehetre, Gajanan T.; Dastager, Syed G.; Dharne, Mahesh S. (Science of the Total Environment, 2019)
Applicability of thermophilic and thereto-tolerant microorganisms for biodegradation of polycyclic aromatic hydrocarbons (PAHs) with low water solubility is an interesting strategy for improving the biodegradation efficiency. In this study, we evaluated utility of thermophilic and thermo-tolerant bacteria isolated from Unkeshwar hot spring (India) for biodegradation of four different PAHs. Water samples were enriched in mineral salt medium (MSM) containing a mixture of four PAHs compounds (anthracene: ANT, fluorene: FLU, phenanthrenc: PHE and pyrene: PYR) at 37 degrees C and 50 degrees C. After growth based screening, four potent strains obtained which were identified as Aeribacillus pallidus (UCPS2), Bacillus axarquiensis (UCPD1), Bacillus siamensis (GHP76) and Bacillus subtilis subsp. inaquosorum (U277) based on the 16S rRNA gene sequence analysis. Degradation of mixed PAH compounds was evaluated by pure as well as mixed cultures under shake flask conditions using MSM supplemented with 200 mg/L concentration of PAHs (50 mg/L of each compound) for 15 days at 37 degrees C and 50 degrees C. A relatively higher degradation of ANT (92% - 96%), FLU (83% - 86%), PHE (16% - 54%) and PYR (51% - 71%) was achieved at 50 degrees C by Aeribacillus sp. (UCPS2) and mixed culture. Furthermore, crude oil was used as a substrate to study the degradation of same PAHs using these organisms which also revealed with similar results with the higher degradation at 50 degrees C. Interestingly, PAH-degrading strains were also positive for biosurfactant production. Biosurfactants were identified as the variants of surfactins (lipopeptide biosurfactants) based on analytical tools and phylogenetic analysis of the surfactin genes. Overall, this study has shown that hot spring microbes may have a potential for PAHs degradation and also biosurfactant production at a higher temperature, which could provide a novel perspective for removal of PAHs residues from oil contaminated sites. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Biodegradation; Biosurfactants; Crude oil; Mixed culture; PAHs; Thermophiles

Novel fatty alkene from marine bacteria: a thermo stable biosurfactant and its applications - Ram, Hari; Sahu, Amit Kumar; Said, Madhukar S.; Banpurkar, Arun G.; Gajbhiye, Jayant M.; Dastager, Syed G. (Journal of Hazardous Materials, 2019)
In this study, a novel thermo stable biosurfactants, 1-Pentanonacontene (C95H190) a fatty alkene and 3-Hydroxy16-methylheptadecanoic acid (C18H36O3) were isolated from a marine isolate SGD-AC-13. Biosurfactants were produced using 1% yeast extract in tap water as production medium at 24 h in flask and 12 h in bioreactor. Using 16S rRNA gene sequence (1515 bp) and BCL card (bioMerieux VITEK (R)), strain was identified as Bacillus sp. Crude biosurfactant reduced the surface tension of distilled water to 31.32 +/- 0.93 mN/m with CMC value of 0.3 mg/ml. Cell free supernatant showed excellent emulsification and oil displacement activity with stability up to 160 degrees C, pH 6-12 and 50 g/L NaCl conc. Biosurfactants were characterized using FTIR, TLC, HPLC LC-MS and NMR spectroscopy. Cell free supernatant reduced the contact angle of distilled water droplet from 117 degrees to 52.28 degrees and of 2% pesticide from 78.77 degrees to 73.42 degrees while 750 mu g/ml of crude biosurfactant reduced from 66.06 degrees to 56.33 degrees for 2% pesticide and recovered 35% ULO and 12% HWCO from the contaminated sand. To our best of knowledge, this is the first report of thermo stable fatty alkene as a biosurfactant and is structurally different from previously reported, with having potential application in agriculture, oil recovery and bioremediation.
Keywords: Bioremediation; Biosurfactants; Fatty alkene; Thermo stability; Wettability